AN INNOVATIVE APPROACH TO EDUCATION AND TRAINING (American Journal of Research in Humanities and Social Sciences, 2024)
This article explores innovative approaches to education and training, focusing on integrating technology, personalized learning, and experiential methods. It analyzes current literature, presents methodologies, and discusses the results and implications for future educational practices.